The recidivism of suicide attempt associated with the severity of depressive symptoms (Research, Society and Development, 2021)
Research aiming to analyze the association between recurrence of suicide attempt and the severity of depressive symptoms. This is an exploratory, descriptive, quantitative research, with data collection carried out between December 2017 and November 2019, in an Emergency Care Unit in Assis / SP. Participated 95 people who were in attendance due to suicide attempt, through interview with semi-structured questionnaire and application of the Beck Depression Inventory. For data analysis, descriptive and inferential statistics were used, using Fisher's exact test and Cramer's V contingency coefficient. The level of significance was set at p